The future of treatment for antiphospholipid syndrome. (February 2014) - Willis, Rohan; Harris, Eon Nigel; Pierangeli, Silvia
Recurrent thrombosis and pregnancy morbidity are the clinical hallmarks of the antiphospholipid syndrome (APS) and occur in the presence of persistent pathogenic antiphospholipid antibodies (aPL). The current approach to the treatment of APS is focused on anticoagulation – as it has been for the past three decades. While some APS patients derive benefit from this approach, there are still a great number who do not and worse, some who suffer severe complications as a result of treatment. As such, there has been much research in the last 30 years aimed at elucidating the pathophysiological mechanisms at play in the development of clinical manifestations in APS. These studies have identified putative molecular targets for aPL action and concordantly enabled the development of therapeutic agents with specific inhibitory activity against these targets. These new targeted therapies are discussed, as well as the role they may play in the future treatment of APS patients.